1976
DOI: 10.21273/jashs.101.4.452
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Evaporative Cooling during Dormancy on ‘Redhaven’ Peach Wood and Fruit Bud Hardiness1

Abstract: ‘Redhaven’ peaches (Prunus persica L. Batsch) were sprinkled from the end of rest, January 22, 1975, until the time check trees reached full bloom, April 18, 1975. Sprinkling delayed bloom by 15 days. Energy models predicted bloom one day before it occurred in the check trees. Wood temperatures were lowered as much as 6.5°C in sprinkled trees, but no significant difference in wood cold hardiness was observed. Sprinkled fruit buds were more cold hardy than non-sprinkled fruit buds until early March. Non-sprinkl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

1978
1978
2000
2000

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 3 publications
(4 reference statements)
0
6
0
Order By: Relevance
“…Effects of evaporative cooling from overhead sprinkling after completion of rest on temperature, development and hardiness of fruit buds demonstrated effective bloom delays of up to 17 days in apples in Utah (1) and 15 days in peaches in Ken tucky (3).…”
mentioning
confidence: 99%
“…Effects of evaporative cooling from overhead sprinkling after completion of rest on temperature, development and hardiness of fruit buds demonstrated effective bloom delays of up to 17 days in apples in Utah (1) and 15 days in peaches in Ken tucky (3).…”
mentioning
confidence: 99%
“…But there was a delay of only 4 to 6 days as calculated from periodic soluble solid measurements during harvest. Bauer et al (5) found no reduction in fruit solids for peaches, but delaying apple bloom (3) reduced soluble solids and consequently maturity by at least 7 days. Therefore, our study indicates a delay in soluble solids in bloom-delayed hedgerow 'Bartlett' and 'Bose' pears comparable to that found for apples (3).…”
Section: Resultsmentioning
confidence: 99%
“…Alfaro et al (3) reported that sprinkling cherry and apple buds delayed bloom 2 weeks and harvest maturity 1 week for both species, but they observed no differences in fruit size or color. Bauer et al (5) observed that bloom delay o f 'Redhaven' peaches did not change sugar or protein levels of the fruit, but reduced yields. Our objectives were to evaluate bloom delay on harvest maturity and quality of 'Bartlett' and 'Bose' pears.…”
mentioning
confidence: 99%
“…Methods for delaying the bloom of peach for frost protec tion have received considerable attention in recent years. The most promising technique appears to be evaporative cooling of the flower buds developed in Utah.2 It has been used with suc cess in dry climates, but has led to serious side effects in more humid areas with heavy soils (1,13). Recently, it has been re ported that the peach seedling rootstock Siberian C causes de lay of bloom in the scion cultivar for up to 6 days (14).…”
mentioning
confidence: 99%